Pengaruh Harga Emas dan Promosi Terhadap Minat Masyarakat pada Tabungan Emas Pegadaian (TEP) di Unit Pegadaian Syariah Manggis Kecamatan Mandiangin Koto Selayan Kota Bukitinggi - Nurkhosyifa Muthia; Amsah Hendri Doni (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
The background of this study is where there should be a slight increase in public interest due to fluctuating gold prices and price differences with conventional pawnshops. As well as the promotion of Pegadaian Gold Savings (TEP) which is less effective carried out by the Pegadaian Syariah Manggis. So that there is a lot of public interest in Pegadaian Gold Savings (TEP) at the Manggis Sharia Pawnshop Unit, Mandiangin Koto Selayan District, Bukitinggi City. The purpose of this study is to find and analyze the effect of gold price (X1) and promotion (X2) on public interest (Y). This type of research is quantitative descriptive where the price of gold (X1) and promotion (X2) affect public interest (Y). The data analysis techniques are Research Instrument Test consisting of Validation and Reliability Test then Classical Assumption Test, namely Autocorrelation Test, Normality, Multicollinearity, heteroscedasticity, and Multiple linear Test, Determination Coefficient Analysis, f Test and t Test. The number of samples that the researchers used was 97 people. The results of the research obtained through the t test, the Gold Price (X1) has a sig value of 0.038 which when compared with the basic requirements for decision making of a sig value of < 0.05, it is certain that the price of gold has a positive effect on public interest (Y). Promotion (X2) has a sig value of 0.000 which when compared to the basic requirements of decision making, namely the sig value of < 0.05, it is certain that the promotion has a positive influence on public interest (Y). As well as the F Test the significance of 0.000 < 0.05 & Fcalculate 17.226 > Ftable 3.09, then there is an effect between the gold price variable simultaneously and the promotion of the interest variable. linear regression of public interest Y = 14.194+0.133 X1+0.291 X2+e